2017
DOI: 10.1186/s12886-017-0480-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow velocity and thickness of the choroid in a patient with chorioretinopathy associated with ocular blunt trauma

Abstract: Background: Choroidal circulation hemodynamics in eyes with ocular blunt trauma has not been quantitatively examined yet. We quantitatively examined changes in choroidal blood flow velocity and thickness at the lesion site using laser speckle flowgraphy (LSFG) and enhanced depth imaging optical coherence tomography (EDI-OCT) in a patient with chorioretinopathy associated with ocular blunt trauma. Case presentation: A 13-year-old boy developed a chorioretinal lesion with pigmentation extending from the optic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, we found that the patients with worse visual outcome appeared to have abnormal ellipsoid zone structure associated with the relatively descending choroidal blood flow. It had been reported that the increase in BCVA accompanied with the improvement in outer retinal morphology was significantly correlated with the macular choroidal circulation elevation in eyes with acute zonal occult outer retinopathy, m u l t i p l e e v a n e s c e n t w h i t e d o t s y n d r o m e , a n d chorioretinopathy associated with ocular blunt trauma [24][25][26]. Furthermore, the choriocapillaris layer beneath the disrupted ellipsoid zone of the photoreceptor had greater areas of flow void than the area beneath an intact ellipsoid zone in ischemic maculopathy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the patients with worse visual outcome appeared to have abnormal ellipsoid zone structure associated with the relatively descending choroidal blood flow. It had been reported that the increase in BCVA accompanied with the improvement in outer retinal morphology was significantly correlated with the macular choroidal circulation elevation in eyes with acute zonal occult outer retinopathy, m u l t i p l e e v a n e s c e n t w h i t e d o t s y n d r o m e , a n d chorioretinopathy associated with ocular blunt trauma [24][25][26]. Furthermore, the choriocapillaris layer beneath the disrupted ellipsoid zone of the photoreceptor had greater areas of flow void than the area beneath an intact ellipsoid zone in ischemic maculopathy [27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the thickness and blood flow velocity concurrently decreased with regression of acute central serous chorioretinopathy (sympathetic pattern) [18, 19]. Moreover, both of the parameters increased with regression of commotio retinae (vaso-occlusive pattern) [20, 21]. Importantly, changes in the thickness and blood flow during disease regression correlated inversely in Vogt-Koyanagi-Harada disease and positively in central serous chorioretinopathy [7, 19].…”
Section: Introductionmentioning
confidence: 99%
“…13,15 The incidence of ERM formation after PPV for a routine RRD repair is reported between 6% and 28.5% and primary ILM peeling at the time of RRD repair has been shown to prevent ERM formation. 12,[14][15][16][17] While previous studies have shown that a large retinal tear may correlate with an ERM formation, 17,18 a report on the incidence of postoperative ERM formation after primary vitrectomy for GRT-RD repair is scarce and yet to be highlighted. We report a retrospective, single-institution, consecutive case series evaluating the incidence of postoperative ERM after primary PPV for GRT-RD repair as well as clinical characteristics and visual outcomes at a level-one trauma and tertiary referral academic center.…”
Section: Introductionmentioning
confidence: 99%